Advanced In Vivo Heteronuclear MRS Approaches for Studying Brain Bioenergetics Driven by Mitochondria - Zhu, Xiao-Hong (Methods Mol Biol, 2009)
The greatest merit of in vivo magnetic resonance spectroscopy (MRS) methodology used in biomedical research is its ability for noninvasively measuring a variety of metabolites inside a living organ. It, therefore, provides an invaluable tool for determining metabolites, chemical reaction rates and bioenergetics, as well as their dynamic changes in the human and animal. The capability of in vivo MRS is further enhanced at higher magnetic fields because of significant gain in detection sensitivity and improvement in the spectral resolution. Recent progress of in vivo MRS technology has further demonstrated its great potential in many biomedical research areas, particularly in brain research. Here, we provide a review of new developments for in vivo heteronuclear (31)P and (17)O MRS approaches and their applications in determining the cerebral metabolic rates of oxygen and ATP inside the mitochondria, in both animal and human brains.